Perencanaan Komunikasi Corporate Social Responsibility Pertamina RU II Sei Pakning dalam Pengembangan Ekowisata Arboretum Gambut - Rizki Mutiara Nizam; Yasir Yasir (President University, 2022)
Pertamina's CSR program through the development of nature conservation-based tourism and education is carried out due to the impact of forest and peatland fires. This study aims to determine the CSR communication planning model of PT Pertamina RU II Sungai Pakning in the development of Marsawa Peat Arboretum Ecotourism. This study uses a qualitative research method with a case study approach. The results of this study indicate that PT Pertamina's CSR communication planning in ecotourism development uses the following steps: problem analysis and research; formulation of communication policies and programs; communication action; and evaluation. Through CSR activities with the community, Pertamina CDO has developed a peat arboretum as a tourist attraction area as a basis for reporting and spreading the image of a company that cares about the environment. The public welcomes the Marsawa peat arboretum ecotourism. Apart from being a tourist attraction, its existence can also provide education and exciting experiences about the importance of protecting the peat environment. The development of peat ecotourism must get support from various stakeholders, especially local governments, so that its existence can have a broad impact on economic development and public awareness of the peat environment.